2022
DOI: 10.1038/s41598-022-07010-z
|View full text |Cite
|
Sign up to set email alerts
|

A sensitivity study of rising compound coastal inundation over large flood plains in a changing climate

Abstract: Coastal flood hazards and damage to coastal communities are increasing steeply and nonlinearly due to the compound impact of intensifying tropical cyclones (TCs) and accelerating sea-level rise (SLR). We expand the probabilistic coastal flood hazard analysis framework to facilitate coastal adaptation by simulating the compound impact of predicted intensifying TCs and rising sea levels in the twenty-first century. We compared the characteristics of landfalling TCs in Florida (FL) and southwest Florida (SWFL) fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…Many studies have started to consider the impact of climate change on compound estuary flooding (Robins et al, 2016;Ghanbari et al, 2021). Outputs of climate models were analysed to show that changes in sea level and precipitation can substantially increase the likelihood of a compound event, where a 100-year event could become a 3-year event by 2100 (Peter Sheng et al, 2022). Model simulations of synthetic storms of combined tropical cyclones and sea level rise in the Cape Fear estuary, North Carolina, have shown that future climatology will increase a 100-year flood extent by 27 % (Gori and Lin, 2022).…”
Section: Future Changes In Floodingmentioning
confidence: 99%
“…Many studies have started to consider the impact of climate change on compound estuary flooding (Robins et al, 2016;Ghanbari et al, 2021). Outputs of climate models were analysed to show that changes in sea level and precipitation can substantially increase the likelihood of a compound event, where a 100-year event could become a 3-year event by 2100 (Peter Sheng et al, 2022). Model simulations of synthetic storms of combined tropical cyclones and sea level rise in the Cape Fear estuary, North Carolina, have shown that future climatology will increase a 100-year flood extent by 27 % (Gori and Lin, 2022).…”
Section: Future Changes In Floodingmentioning
confidence: 99%
“…These products are produced using an integrated modeling system, CH3D-SWAN-WARMER, based on the coupling of a three-dimensional vegetation-resolving hydrodynamic-wave model, CH3D-SWAN [46], and a vegetation model, WARMER [47]. Probabilistic coastal flood maps incorporating the effects of sea-level rise and surges and waves are produced using the JPM-OS statistical method [48] and ensembles of tropical cyclones based on historical data, as well as predictions of the best available climate models [49,50]. The ACUNE Geo Tool provides current and future 1% annual exceedance probability flood elevation (commonly referred to as 100-year flood or Base Flood Elevation) for adaptation planning.…”
Section: Acune Geo Toolmentioning
confidence: 99%
“…Therefore, ACUNE provides compound flood maps due to tides and SLR, as well as compound flood maps due to future storms and SLR. The effect of rainfall on coastal flooding in this region was found to be relatively unimportant [50], hence inland flooding was not included in the current effort. Existing SLR Geo Tools, however, typically only consider flood maps due to SLR alone.…”
Section: Acune Geo Toolmentioning
confidence: 99%
“…Many studies have started to consider the impact of climate change on compound estuary flooding (Robins et al, 2016;Ghanbari et al 2021). Outputs of climate models were analysed to show that changes in sea level and precipitation can substantially increase the likelihood of a compound event, where a 100-year event could become a 3-year event by 2100 (Sheng et al, 2022). Model simulations of synthetic storms of combined tropical cyclones and sea-level rise in Cape Fear Estuary, North Carolina, have shown that future climatology will increase a 100-year flood extent by 27 % (Gori and Lin, 2022).…”
Section: Future Changes In Floodingmentioning
confidence: 99%